Development of methodical approaches to quantitative assessment of the region reputation - Safiullin, Marat R.; Grunichev, Alexander S. (Opción, 2019)
The research aims to investigate the development of the theory of the reputation economy in relation to regional economic systems. The research method is based on the use of tools for economic and mathematical analysis of a wide range of data characterizing the reputation activity of regional systems. As a result, a number of the Volga Federal District regions need a substantial adjustment of the state policy. In conclusion, the developed methodological approaches form an important foundation in the formation of economic and mathematical models contributing to the solution of such an important task in economic theory.